Answer to Question #12176 in Trigonometry for sathya krishna sai
prove that sin(A)-sin(B)/cos(A)+cos(B) + cos(A)-cos(B)/sin(A)+sin(B)=0
1
2012-07-24T11:25:47-0400
[sin(A)-sin(B)]/[cos(A)+cos(B)] +
[cos(A)-cos(B)]/[sin(A)+sin(B)]=
=[sin^2(A)-sin^2(B)+
cos^2(A)-cos^2(B)]/[(sin(A)+sin(B))(cos(A)+cos(B))] =
=(1-1)/
[(sin(A)+sin(B))(cos(A)+cos(B))] =0
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment